Textured and Hierarchically Porous Hematite Photoanode for Efficient Hydrogen Production via Photoelectrochemical Hydrazine Oxidation - Tan, Runfa; Jeong, Yoo Jae; Han, Hyun Soo; Kapse, Samadhan; Shin, Seong Sik; Zheng, Xiaolin; Cho, In Sun (Nano-Micro Letters, 2026)
The performance of hematite (α-Fe2O3) photoanodes for photoelectrochemical (PEC) water splitting has been limited to around 2–5 mA cm−2 under standard conditions due to their short hole diffusion length and sluggish oxygen evolution reaction kinetics. This work overcomes those challenges through a synergistic strategy that co-designs the hematite architecture and the surface reaction pathway. We introduce a textured and hierarchically porous Ti-doped Fe2O3 (tp-Fe2O3) photoanode, synthesized via multi-cycle growth and flame annealing method. This unique architecture features a high texture (110), enlarged surface area, and hierarchically porous structure, which enable significantly enhanced bulk charge transport and interfacial charge transfer compared to typical nanorod Ti-doped Fe2O3 (nr-Fe2O3). As a result, the tp-Fe2O3 photoanode achieves a photocurrent density of 3.1 mA cm−2 at 1.23 V vs. RHE with exceptional stability over 105 h, notably without any co-catalyst. By replacing the OER with the hydrazine oxidation reaction, the photocurrent further reaches a record-high level of 7.1 mA cm−2 at 1.23 VRHE. Finally, when we integrate the tp-Fe2O3 with a commercial Si solar cell, it achieves a solar-to-hydrogen efficiency of 8.7%—the highest reported value for any Fe2O3-based PV-tandem system. This work provides critical insights into rational Fe2O3 photoanode design and highlights the potential of hydrazine as an efficient alternative anodic reaction, enabling waste valorization. Highights: 1 A multi-cycle growth and flame annealing strategy was developed to construct textured and hierarchically porous Ti-doped hematite (tp-Fe2O3) photoanodes with enhanced charge transport and surface kinetics. 2 The hydrazine oxidation reaction was introduced as a fast and thermodynamically favorable alternative to the oxygen evolution reaction, enabling the simultaneous production of hydrogen and the remediation of toxic hydrazine. 3 The tp-Fe2O3-based bias-free photovoltaic-photoelectrochemical tandem device achieved a record solar-to-hydrogen efficiency of 8.7%, demonstrating excellent stability and scalability for sustainable solar fuel generation.